2013
DOI: 10.1111/sdi.12054
|View full text |Cite
|
Sign up to set email alerts
|

Using an Electronic Self‐Management Tool to Support Patients with Chronic Kidney Disease (CKD): A CKD Clinic Self‐Care Model

Abstract: New healthcare delivery models are needed to enhance the patient experience and improve quality of care for individuals with chronic conditions such as kidney disease. One potential avenue is to implement self-management strategies. There is growing evidence that self-management interventions help optimize various aspects of chronic disease management. With the increasing use of information technology (IT) in health care, chronic disease management programs are incorporating IT solutions to support patient sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 45 publications
(50 reference statements)
1
45
0
5
Order By: Relevance
“…This shift in focus has resulted in a growing emphasis on patient engagement and the incorporation of digital solutions to support patient self-management practices (15,16). Individuals with CKD, often characterized by low disease awareness, limited health literacy, and frequent interactions with the health care system (17,18), are at high risk of adverse safety events related to their care, such as drug-related problems.…”
Section: Discussionmentioning
confidence: 99%
“…This shift in focus has resulted in a growing emphasis on patient engagement and the incorporation of digital solutions to support patient self-management practices (15,16). Individuals with CKD, often characterized by low disease awareness, limited health literacy, and frequent interactions with the health care system (17,18), are at high risk of adverse safety events related to their care, such as drug-related problems.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic kidney disease self-management has a substantial number of daily tasks that a person needs to perform to manage the impact of the disease and to slow its progression (Curtin, Mapes, & Thomas-Hawkins, 2001;Lin, Wu, Wu, Chen, & Chang, 2012;Ong, Jassal, Porter, Logan, & Miller, 2013). The following sections review the previously described skills in the context of the CKD self-management.…”
Section: Skillsmentioning
confidence: 99%
“…In addition, Lin et al (2012) and Ong et al (2013) have indicated other components also needed in self-management in people with CKD. Lin et al (2012) used Lorig and Holman (2003) components of self-integration, problem solving, social support, and taking action.…”
Section: 42mentioning
confidence: 99%
See 2 more Smart Citations